Severe Ascites Appears in A Case of Hepatic Tuberculosis: A Case Report - Widiyastuti, Krisnina Nurul; Kholili, Ulfa (Journal of Neonatal Surgery, 2025)
Hepatic tuberculosis has non-specific symptoms, challenging diagnosis, and may lead to mismanagement, particularly in endemic tuberculosis. Although severe ascites can appear in hepatic tuberculosis, it can also occur in other forms of tuberculosis, especially hepatobiliary and peritoneal tuberculosis. Meanwhile, the gold standard of the diagnosis is using a biopsy. Despite the negative results for tuberculosis in the biopsy, an alternative diagnosis can help establish the diagnosis of hepatic tuberculosis using GeneXpert and culture on hepatic tissue, in which a confirmed negative result for tuberculosis in other areas. Although identifying individuals with potential tuberculosis was challenging in the endemic area, it is crucial to undergo thorough and conscientious examinations for tuberculosis, which include radiological imaging and nonspecific clinical appearance, especially gross ascites.